Cattle farming, armed conflict, and climate change: Possibilities and limitations in a case study in the Colombian Amazon - Castillo Sanchez, Verenice; Orduz Ramos, Daniela; Pazos Cardenas, Mateo; Triana Ángel, Natalia (2024)
The Colombian armed conflict has long impacted both the population and the country's productive systems. However, the signing of the Peace Agreement between the Colombian State and the FARC-EP in 2016 has introduced new possibilities. While violence persists, particularly involving other armed actors connected to drug trafficking, there has been a push for productive projects supported by the State and international cooperation. These initiatives aim to enhance agricultural and livestock value chains in rural areas affected by the conflict, such as the Colombian Amazon. Our study delves into the dynamics of armed conflict and its impact on dairy farmers and milk production and explores perceptions of climate change and the adoption of sustainable technologies for mitigation and adaptation in the municipality of Puerto Rico (in the Caquetá department of the Colombian Amazon region, one of the most severely affected areas not only by violence but also by deforestation). Using qualitative methods including workshops, focus groups, and key informant interviews with 32 cattle farming families, we found that traditional cattle systems in the region leave small producers particularly vulnerable to extreme weather events, with limited access to adaptation strategies. Their ability to adapt depends on the availability of various forms of natural, physical, and social capital. Recognizing climate change adaptation as a multifaceted issue is crucial and requires the incorporation of this understanding into the development of tailored strategies, technologies, and practices that consider the needs, contexts, and perspectives of affected populations. Additionally, understanding how conflict has influenced agricultural management and practices provides insight into the resilience and identity of rural people. This sheds light on why these areas, despite isolation, low productivity, conflict, armed presence, and challenging living conditions, are still seen by farmers as their place to be.